1999
DOI: 10.1042/bj3410537
|View full text |Cite
|
Sign up to set email alerts
|

Adenylosuccinate synthase from Saccharomyces cerevisiae: homologous overexpression, purification and characterization of the recombinant protein

Abstract: Adenylosuccinate synthase (EC 6.3.4.4) catalyses the first committed step in the synthesis of adenosine. We have overexpressed the cloned gene of Saccharomyces cerevisiae (ADE12) in S. cerevisiae. The recombinant enzyme exhibits similar kinetic behaviour to that of the native enzyme purified from S. cerevisiae. This ter-reactant dimeric enzyme shows Michaelis-Menten kinetics only with IMP. L-Aspartate and GTP display a weak negative co-operativity (Hill coefficient 0.8-0.9). This negative co-operativity has no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…In yeast, ADE12 encodes the adenylosuccinate synthase (AdSS) involved in the de novo synthesis of AMP from IMP (Lipps & Krauss, 1999). FgADE12 (FGSG_05187) is the ortholog of ADE12 in F. graminearum and has conserved domain sequences and active sites of AdSS (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In yeast, ADE12 encodes the adenylosuccinate synthase (AdSS) involved in the de novo synthesis of AMP from IMP (Lipps & Krauss, 1999). FgADE12 (FGSG_05187) is the ortholog of ADE12 in F. graminearum and has conserved domain sequences and active sites of AdSS (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…10 IMP•GTP•MjADSS: 6-pIMP Formation Occurs in the Absence of L-Aspartate. Extensive kinetic studies of ADSSs from various organisms such as E. coli, 32 mouse, 8 Zea mays, 33 and Saccharomyces cerevisiae 34 suggest that IMP and GTP bind in random order to the enzyme at distinct binding sites. Once both ligands are bound, structural studies show that the first catalytic intermediate, 6-pIMP, is formed even in the absence of L-aspartate in these enzymes.…”
Section: ■ Resultsmentioning
confidence: 99%
“…Extensive kinetic studies of ADSSs from various organisms such as E. coli , mouse, Zea mays , and Saccharomyces cerevisiae suggest that IMP and GTP bind in random order to the enzyme at distinct binding sites. Once both ligands are bound, structural studies show that the first catalytic intermediate, 6-pIMP, is formed even in the absence of l -aspartate in these enzymes. , By contrast, in MjADSS, it was reported that the presence of HDA was required for complete utilization of GTP, which was implicated in the formation of 6-pIMP .…”
Section: Resultsmentioning
confidence: 99%
“…Steady-State Enzyme Kinetics and Inhibitor Analysis. All enzyme assays were performed as previously described 38 with some modifications. Enzymatic assays were performed at 25 °C in triplicate by monitoring the production of adenylosuccinate at 280 nm (ε = 11.7 mM −1 cm −1 ) for 5 min using a Varian Cary 60 spectrophotometer (Agilent Technologies, USA).…”
Section: ■ Discussionmentioning
confidence: 99%